Risk factors for myocardial injury and death in patients with COVID-19: insights from a cohort study with chest computed tomography. Issue 14 (8th July 2020) - Ferrante, Giuseppe; Fazzari, Fabio; Cozzi, Ottavia; Maurina, Matteo; Bragato, Renato; D'Orazio, Federico; Torrisi, Chiara; Lanza, Ezio; Indolfi, Eleonora; Donghi, Valeria; Mantovani, Riccardo; Liccardo, Gaetano; et al.
Abstract: Aims: Whether pulmonary artery (PA) dimension and coronary artery calcium (CAC) score, as assessed by chest computed tomography (CT), are associated with myocardial injury in patients with coronavirus disease 2019 (COVID-19) is not known. The aim of this study was to explore the risk factors for myocardial injury and death and to investigate whether myocardial injury has an independent association with all-cause mortality in patients with COVID-19. Methods and Results: This is a single-centre cohort study including consecutive patients with laboratory-confirmed COVID-19 undergoing chest CT on admission. Myocardial injury was defined as high-sensitivity troponin I >20 ng/L on admission. A total of 332 patients with a median follow-up of 12 days were included. There were 68 (20.5%) deaths; 123 (37%) patients had myocardial injury. PA diameter was higher in patients with myocardial injury compared with patients without myocardial injury [29.0 (25th–75th percentile, 27–32) mm vs. 27.7 (25–30) mm, P < 0.001). PA diameter was independently associated with an increased risk of myocardial injury [adjusted odds ratio 1.10, 95% confidence interval (CI) 1.02–1.19, P = 0.01] and death [adjusted hazard ratio (HR) 1.09, 95% CI 1.02–1.17, P = 0.01]. Compared with patients without myocardial injury, patients with myocardial injury had a lower prevalence of a CAC score of zero (25% vs. 55%, P < 0.001); however, the CAC score did not emerge as a predictor of myocardial injury by multivariable logistic regression. Myocardial injury was independently associated with an increased risk of death by multivariable Cox regression (adjusted HR 2.25, 95% CI 1.27–3.96, P = 0.005). Older age, lower estimated glomerular filtration rate, and lower PaO2 /FiO2 ratio on admission were other independent predictors for both myocardial injury and death. Conclusions: An increased PA diameter, as assessed by chest CT, is an independent risk factor for myocardial injury and mortality in patients with COVID-19. Myocardial injury is independently associated with an approximately two-fold increased risk of death.